2021
DOI: 10.1088/1748-9326/ac09b0
|View full text |Cite
|
Sign up to set email alerts
|

Forested lands dominate drinking water supply in the conterminous United States

Abstract: Forests provide the most stable and highest quality water supplies among all land uses. Quantitatively evaluating the benefits of forest water supply functions is important to effectively mitigate the impacts of land development, climate change, and population growth. Here, by integrating a water balance model and national drinking water data, we determined the amount of surface water yield originating on different forest ownership types at a fine resolution (88,000 watersheds) and tracked that water through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 37 publications
4
21
0
Order By: Relevance
“…The negative relationship of our most influential variable, forest‐dominated land cover, to percent surface water supports the results of other studies (Liu et al., 2021; Lockaby et al., 2013; Tulbure & Broich, 2019). There are conflicting accounts on whether forestation increases or decreases streamflow and surface water resources, indicating that there are likely other factors at play (Zeng et al., 2020; Zhang et al., 2017; Zhang & Wei, 2021).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The negative relationship of our most influential variable, forest‐dominated land cover, to percent surface water supports the results of other studies (Liu et al., 2021; Lockaby et al., 2013; Tulbure & Broich, 2019). There are conflicting accounts on whether forestation increases or decreases streamflow and surface water resources, indicating that there are likely other factors at play (Zeng et al., 2020; Zhang et al., 2017; Zhang & Wei, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…Li et al, 2020;Zhang & Wei, 2021). Specifically, studies in the southeastern U.S., Mexico, and China found that forest-dominated land cover diminishes runoff and improves water quality (Liu et al, 2021;Orozco et al, 2020;Zeng et al, 2020). Less variability in surface water in response to forest-dominated land cover supports the negative relationship we found between percent forest-dominated land cover and percent surface water area.…”
Section: Drivers Of Surface Watersupporting
confidence: 70%
“…Forested lowland and mountain ecosystems are the highest source area of renewable freshwater, providing 57% and 28% of total global runoff respectively as well as renewable water supplies to two-thirds of the world's population [5]. Forested areas contribute disproportionately to surface water yield within the conterminous United States [46]. Areas with higher forested area have been linked to higher fish biodiversity in neotropical environments, likely due to the diversity of habitats that can be developed and supported by forests [47].…”
Section: Discussionmentioning
confidence: 99%
“…The WaSSI model has been tested, validated, and compared to other water balance models (Caldwell et al., 2012, 2015, 2020; Li et al., 2020; Schwalm et al., 2015; G. Sun et al., 2011). It has been used in several regional and national scale water resource assessments (Duan et al., 2018, 2019; Li et al., 2020; Lockaby et al., 2013; Marion et al., 2013; S. Sun et al., 2016; Tavernia et al., 2013), in examining the water‐energy nexus at the national scale (Averyt et al., 2011), in quantifying surface water supplied by National Forests (Caldwell et al., 2014) and State and private forests in the South (Liu et al., 2020) and across the CONUS (Liu et al., 2021), and in studying the impacts of historical drought on National Forests and Grasslands across the CONUS (S. Sun et al., 2015a, 2015b).…”
Section: Methodsmentioning
confidence: 99%
“…Our previous study shows that over half of the U.S. population benefits from water originating from forested lands because forests are often found in areas with high precipitation and are regarded as “water towers” (Liu et al., 2021). Although water supply has been recognized as a critical factor for National Forest management, privately owned forests are the most vulnerable to future land use change and associated water supply impacts (Liu et al., 2021). Most of the public forests lie in the 11 contiguous western states, while privately owned forests are the dominant forested lands in the eastern U.S. For example, forests owned by corporations, families, and other private entities account for about 80% of the total forested land area across the South (Liu et al., 2020).…”
Section: Introductionmentioning
confidence: 99%